INFLUENCE OF MICROBIAL WOUND DISSEMINATION AND MICROCIRCULATION ON THE RESULTS OF SKIN ENGRAFTMENT - Yu. V. Yurova; I. V. Shlyk (Вестник хирургии имени И.И. Грекова)
The indices of Doppler laser flowmetery are proposed to be used for determination of the readiness of a granulating wound for free autoplasty. An analysis of capillary blood flow in the groups under test showed the information value of indicators of microcirculation obtained by Doppler laser flowmetery for determination of the granulating wound condition before autotransplantation and prediction of the results of skin engraftment. It is stated, that the disorder of microcirculation has been developed against the background of progression of wound invasive infection. The obtained data can allow the development of an algorithm of treatment and the preparation of the patients to surgery, determination of the terms of operation, the development the strategy of postoperative management of the patients, which can reduce unfavorable results of operations.